The Impact of COVID-19 Crisis upon the Effectiveness of E-learning in Higher Education Institution - Sharina Osman; Muna Norkhairunnisak Ustadi; Hanna Kamila Zahrol Kamar; Nur Hasliza Johari; Nur ‘Amirah Ismail (Journal of Information Technology Management)
The infestation of the world pandemic has significantly changed the landscape of teaching and learning experience in Malaysia.  Particularly for the institution under study, E-learning, previously used as the support medium to face-to-face classroom teaching, has become the primary medium of teaching and learning amid Covid-19.  E-learning platform has replaced the face-to-face classes. Even though it is only a temporary approach, less is known in terms of its effectiveness.  The present paper intends to examine the factors contributing to E-learning's effectiveness in a Higher Education Institution in Malaysia amid the COVID-19 crisis. The Technology Acceptance Model underpinned the conceptual framework.   This study investigated the relationship between the independent variables (perceived usefulness, perceived ease of use, and self-motivation) and E-learning effectiveness.  The data were collected through an online self-administrated questionnaire using Google form and received a total of 354 respondents.  The data were analyzed using SPSS and Smart PLS.  The findings revealed that perceived usefulness, perceived ease of use, and self-motivation positively influenced E-learning's effectiveness.  This paper concluded that regardless of whether as the support medium or the primary medium in the teaching and learning process, the determinant to E-Learning effectiveness is still perceived the same. This study also supports the TAM proposition while incorporate self-motivation in measuring learning effectiveness.